THE PASANG RI KAJANG: CHALLENGES AND DYNAMICS OF EDUCATION IN THE INDIGENOUS COMMUNITY OF KAJANG, SOUTH SULAWESI, INDONESIA - Hafid, Abdul; Suardi, Suardi; Kaharuddin, Kaharuddin (Universitas Islam Negeri Raden Intan Lampung, 2023)
Pasang is a cultural product that contains the results of ancestral messages containing good knowledge in aspects of human life in this world and the afterlife. Pasang symbolizes experience, knowledge, and education inherent in the Kajang indigenous people. Therefore, it is always part of their way of life that influences their daily activities. This article aims to discuss Pasang: Challenges and Dynamics of Education in the Kajang Indigenous Community, South Sulawesi. This research uses qualitative methods, where the data is collected through observation, interviews, and documentation of research objects to be processed descriptively. Using the social science, anthropology, and ethnographic approach, this article shows the important position of Pasang for the Kajang indigenous community and the challenges and dynamics in education development in Indonesia. This article shows that Pasang is a cultural product that is in harmony with educational practices, formal and informal, but often clashes with structural, legal, and normative processes, for example, in educational institutions. The main result presented in this article is that Pasang can survive along with the modernization process despite various inhibiting and supporting factors. Another interesting thing is the value and meaning of Pasang, which is expected to go hand in hand with the world of education, which is structural, legal, and formal. Thus, Pasang does not eliminate the main function as a cultural and educational product among the indigenous community of Kajang.